Pengaruh Berbagai Konsentrasi Benzil Adenin dan Asam Naftalen Asetat Pada Kultur In vitro Singkong (Manihot esculenta Crantz.) - Ardian Ardian; Kresna Kresna; Agustiansyah Agustiansyah (Jurnal Penelitian Pertanian Terapan, 2012)
Propagation of cassava through in vitro culture is needed by farmers and agro industries to fulfill the need of the best and the newest clone as soon as after it is released by government. The objective of this research was to know the effects of the application of some concentrations of benzyl adenine and naphthalene acetic acid on in vitro growth and multiplication of micro-shoot of cassava. Explants used were one-node green cuttings of cassava, which were derived from cutting seedling. This research was arranged in completely randomized design with the treatments consisting of some concentrations of benzyl adenine 0.2, 0.4, and 0.8 mg/l and concentrations of naphthalene acetic acid: 0 and 0.1 mg/l. Each treatment was replicated 10 times with 2 explants in each experiment unit. The best growth and multiplication shoot of cassava in vitro was achieved by treatment of 0,2 mg/l benzyl adenine with 0,1 mg/l naphthalene acetic acid. Keywords: Benzyl Adenine, Naphthalene Acetic Acid, Cassava